A New Framework for Mitigating Voltage Regulation Issue in Active Distribution Systems Considering Local Responsive Resources - Sajjad Fattaheian-Dehkordi (IEEE, 2021)
Recently, renewable energy sources (RESs) have increasingly being integrated into the power grids as a result of environmental and governmental perspectives. In this regard, the installation of RESs as potential power sources in active distribution systems would benefit the grid by decreasing the power losses, as well as addressing the fossil fuel shortages, and their environmental aspects. Nevertheless, the high-level integration of RESs as well as the development of distributed formations in local systems could challenge the reliable operation of the grid. In this context, conventional approaches could not optimally mitigate the regulation-voltage issue; therefore, utilities have to exploit the scheduling of local responsive sources to address the regulation-voltage issue in systems with high-level penetration of RESs. Consequently, the offered scheme in this paper enables the system operator to activate flexibility service from local responsive sources with the aim of addressing the regulation-voltage issue in the grid. Respectively, the system operator as the leader provides incentive control signals to ensure collaboration of the independent agents in voltage regulating procedure. Finally, the developed framework is applied on the 37-bus IEEE test network to investigate its application in mitigating the regulation-voltage issue in the active distribution systems with multi-agent formations.